Mobilisasi Dini sebagai upaya dalam mengatasi Gangguan mobilitas Fisik Pada Ibu Post Operatif Sectio Caesarea - Aisyah, Aisyah; Suparno, Suparno; Estiani, Meilina; Sawitri, Endah ayu (NHM PRESS, 2023)
The problem that is often felt in post sectio caesarea patients is impaired physical mobility. Early mobilization post sectio caesarea should be carried out to prevent immobilization complications. This study aims to implement early mobilization in post sectio caesarea patients. The design of this study uses a descriptive method in the form of a case study with a nursing process approach. Nursing care was given to 2 post sectio caesarea women with impaired physical mobility. This case study explores nursing care for post SC patients who experience impaired physical mobility through teaching early mobilization and providing health education about early mobilization.The results showed that after the implementation, the client was able to fulfill his activity needs independently, even though there were slight obstacles to one of the clients at one of the stages. The conclusion of the researchers is that mobilization support can be used as a nursing intervention to increase movement and independence in mothers with postoperative sectio caesarea.